PENTINGNYA PENERAPAN SISTEM INFORMASI AKUNTANSI PENJUALAN 4.0 DAN PENGENDALIAN INTERNAL PADA PT X SURABAYA DI SAAT PANDEMI COVID 19 UNTUK MENGATASI JURANG KEBANGKRUTAN - Richard Andrew (Jurnal Akuntansi dan Pajak, 2022)
In the midst of the covid 19 pandemic, many companies are experienced problems in their sales system, many company profits continued to decline until bankruptcy in implementation of activity restrictions on community activities. Therefore good internal control is needed. The purpose of this study is to determine the importance of internal control in the company’s sales system. The research method used is descriptive qualitative. Data obtained directly at the company PT X Surabaya. The result of the study obtained the effect of internal control on the threat of sales accounting information systems. The conclusion of the study is the importance of internal control to improve the performance of the sales accounting information system at PT X Surabaya in the midst of the covid 19 pandemic.